Mapping of Sea Surface Temperature Distribution, Sibolga City, North Sumatera Province using NOAA/AVHRR Satellite - Ogesnain Sinaga; Mubarak Mubarak; Elizal Elizal (Ilmu Perairan (Aquatic Science), 2021)
The research was aimed to map the sea surface temperature (SST) distribution in Sibolga waters that based on 20 years satellite image of NOAA/AVHRR. It used survey method for ground check in the field to collect in situ SST and other seawater parameters such as its visibillity, pH, and salinity. It found that the SST changes on each 5 year’s calculations with different pattern of distribution; the figures of SST ranged between 28.5-30  oC, 30.5-31  oC, 27-29  oC, and 27.5-28.5 oC. In addition, the pH of seawater ranged from 6-7 and 27-30 ppt in average. Different pattern of SST distribution might be related to global change on temperature and season over 20 years of study.